The Development of Cognitive Training in Older Persons with Mild Neurocognitive Disorder in Kutpong Subdistrict, Muang Loei District, Loei Province - Termpornlerd , Preechya; Pawanlanchakorn , Jureerat (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2025)
The prevalence of mild neurocognitive disorder among older adults is currently increasing. Effective management strategies may reduce the progression to dementia in the future. This research and development research aimed to develop and study the effects of the cognitive training model in older persons with mild neurocognitive disorder in Kutpong Subdistrict, Muang Loei District, Loei Province. The study involved 10 older adults diagnosed with mild neurocognitive disorder according to the DSM-V criteria. The research was conducted in four phases: the first phase involved in-depth interviews with healthcare professionals specializing in elderly care to gather situational data; the second phase focused on the development of the cognitive training model; the third phase assessed the effects of the model; and the fourth phase aimed to refine the model and propose it as a guideline for the province. Data collection methods included in-depth interviews, pre- and post-assessment using the MoCA-B test, and satisfaction surveys. Data analysis employed frequency, percentage, mean, standard deviation, and paired t-test methodologies. The results from the in-depth interviews revealed a consensus that the province currently lacked a suitable cognitive training model for older adults with mild neurocognitive disorder. A new cognitive training model had been developed based on a review of the literature and the insights gained from these interviews, with the TEAMV (Training for Executive function, Attention, Memory, and Visuospatial functions) program selected for inclusion. This program involved six consecutive group sessions, each lasting three hours, conducted weekly over a six-week period. The post-test results showed a significant improvement in the average cognition score of the sample group, with a mean score of 24.60 (S.D. = 3.72) compared to a pre-test mean score of 19.70 (S.D. = 3.47), with statistical significance (p < .001). These findings suggest this cognitive stimulation model is likely to enhance cognitive performance in individuals with mild neurocognitive disorder. This may be utilized as a framework for advancing cognitive potential among elderly individuals with mild neurocognitive disorder in Loei Province in the future.